Machine Intelligence and Big Data in Industry - Ryżko, Dominik; Gawrysiak, Piotr; Kryszkiewicz, Marzena; Rybiński, Henryk; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents valuable contributions devoted to practical applications of Machine Intelligence and Big Data in various branches of the industry. All the contributions are extended versions of presentations delivered at the Industrial Session the 6th International Conference on Pattern Recognition and Machine Intelligence (PREMI 2015) held in Warsaw, Poland at June 30- July 3, 2015, which passed through a rigorous reviewing process. The contributions address real world problems and show innovative solutions used to solve them. This volume will serve as a bridge between researchers and practitioners, as well as between different industry branches, which can benefit from sharing ideas and results.
Text Processing -- Data Mining -- Text and Multimedia Processing -- Software -- Complex Systems, Internet of Things and Agent Systems.
Keywords: Computational intelligence; Data mining; Quantitative research; Industrial engineering; Production engineering; Computational Intelligence; Data Mining and Knowledge Discovery; Data Analysis and Big Data; Industrial and Production Engineering